Scale Invariance of Albedo‐Based Wind Friction Velocity. Issue 16 (18th August 2020) - Ziegler, Nancy P.; Webb, Nicholas P.; Chappell, Adrian; LeGrand, Sandra L.
Abstract: Obtaining reliable estimates of aerodynamic roughness is necessary to interpret and accurately predict aeolian sediment transport dynamics. However, inherent uncertainties in field measurements and models of surface aerodynamic properties continue to undermine aeolian research, monitoring, and dust modeling. A new relation between aerodynamic shelter and land surface shadow has been established at the wind tunnel scale, enabling the potential for estimates of wind erosion and dust emission to be obtained across scales from albedo data. Here, we compare estimates of wind friction velocity ( u * ) derived from traditional methods (wind speed profiles) with those derived from the albedo model at two separate scales using bare soil patch (via net radiometers) and landscape (via Moderate Resolution Imaging Spectroradiometer [MODIS] 500 m) data sets. Results show that profile‐derived estimates of u * are highly variable in anisotropic surface roughness due to changes in wind direction and fetch. Wind speed profiles poorly estimate soil surface (bed) wind friction velocities necessary for aeolian sediment transport research and modeling. Albedo‐based estimates of u * at both scales have small variability because the estimate is integrated over a defined, fixed area and resolves the partition of wind momentum between roughness elements and the soil surface. We demonstrate that the wind tunnel‐based calibration of albedo for predicting wind friction velocities at the soil surface ( u s* ) is applicable across scales. The albedo‐based approach enables consistent and reliable drag partition correction across scales for model and field estimates of u s* necessary for wind erosion and dust emission modeling. Key Points: First field test of albedo approach to estimate total and surface friction velocities over a rough bed Albedo‐derived estimates of total friction velocity were consistent with friction velocities obtained from wind speed profiles Field measurements of surface wind friction velocities consistent with wind tunnel data, confirming the albedo approach is scale invariant